Catalase Biomimetic Sensor Based on Metal - Malikova Nurana Nahmad; Gurbanova Lala Maharram; Ali-Zadeh Nahmad Islam; Nagiev Tofik Murtuza; Shokhzod Ulashov; Kurbanova Shaxnoza (BIO Web of Conferences)
The development of motivated biosensors associated with the study of a large number of different substances is one of the most important areas of development of analytical chemistry. This goal in the development of certain biosensors was necessary for a sufficiently clear, fast, qualitative and quantitative determination of the desired component. Chemical reactions in living organisms are carried out with the help of catalysts - enzymes. Enzymes are proteins with prosthetic groups, and proteins are polymers formed from amino acid links. The number of different enzymes in a cell is the same as the number of different chemical reactions that occur in it. This work is devoted to the study of biomimetic sensors, where metals (Pb, Ag, Al) were used as a converter. The active material was iron tetraphenylporphyrin adsorbed on Al2O3. It was found that biomimetic sensors made on the basis of intelligent material (TPhPFe3+/Al2O3) and metals have a number of technological advantages. The developed biomimetic sensors are characterized by high sensitivity, activity, stability and reproducibility. When detecting the catalase activity of biomimetic sensors, the maximum sensitivity to the concentration of H2O2 in an aqueous solution for TPhPFe3+/Al2O3//Pb was 10-8wt.%, for TPhPFe3+/Al2O3//Ag – 10-8wt.%, for TPhPFe3+/Al2O3//Al – 10-6 wt.%.